A homozygous B3GAT3 mutation causes a severe syndrome with multiple fractures, expanding the phenotype of linkeropathy syndromes. (18th June 2015) - Jones, Kelly L.; Schwarze, Ulrike; Adam, Margaret P.; Byers, Peter H.; Mefford, Heather C.
<x xml:space="preserve">Abstract</x> Linkeropathies are a group of syndromes characterized by short stature, radio‐ulnar synostosis, decreased bone density, congenital contractures and dislocations, joint laxity, broad digits, brachycephaly, small mouth, prominent eyes, short or webbed neck, congenital heart defects and mild developmental delay. Linkeropathies are due to enzymatic defects in the synthesis of the common linker region that joins the core proteins to their glycosaminoglycan (GAG) side chains. The enzyme glucuronyltransferase 1, encoded by B3GAT3, adds the last four saccharides comprising the linker region. Mutations in B3GAT3 have been reported in two unrelated families with the same homozygous mutation (c.830G>A, p.Arg277Gln). We report on a patient with a novel homozygous B3GAT3 (c.667G>A, p.Gly223Ser) mutation and a history of multiple fractures, blue sclerae, and glaucoma. Our patient was a 12‐month‐old boy born to consanguineous parents and, like previously reported patients, he had bilateral radio‐ulnar synostosis, severe osteopenia, an increased gap between first and second toes, bilateral club feet, and atrial and ventricular septal defects. He had the additional features of bilateral glaucoma, hypertelorism, upturned nose with anteverted nares, a small chest, a diaphragmatic hernia, multiple fractures, arachnodactyly, overlapping fingers with ulnar deviation, lymphedema, hypotonia, hearing loss, and perinatal cerebral infarction with bilateral supra‐ and infratentorial subdural hematomas. We highlight the extended phenotypic range of B3GAT3 mutations and a provide comparative overview of the phenotypic features of the linkeropathies associated with mutations in XYLT1, B4GALT7, B3GALT6, and B3GAT3. © 2015 Wiley Periodicals, Inc.